Beethoven's Conversation Books - Beethoven, Ludwig van 1770-1827; Albrecht, Theodore (Woodbridge, Suffolk The Boydell Press, 2018)
"Ludwig van Beethoven (1770-1827) is recognized the world over as a composer of musical masterpieces exhibiting heroic strength, particularly in the face of his increasing deafness from ca. 1798. By 1818, the Viennese composer had begun carrying blank booklets with him, for his acquaintances to jot their sides of conversations, while he answered aloud. Often, he himself used the pocket-sized booklets to make shopping lists and other reminders, including occasional early sketches for his compositions. Today, 139 of these booklets survive, covering the years 1818 up to the composer's death in 1827 and including such topics as music, history, politics, art, literature, theatre, religion, and education as perceived on a day-to-day basis in post-Napoleonic Europe. An East German edition, begun in the 1960s and essentially complete by 2001, represents a diplomatic transcription of these documents. It is a masterpiece of pure scholarship but is difficult to use for anyone who is not a specialist. Moreover, Beethoven scholarship has moved on significantly since the long-ranging genesis of the German edition. These important booklets are here translated into English in their entirety for the first time. The volumes in this series include an updated editorial apparatus, with revised and expanded notes and many new footnotes exclusive to this edition, and brand new introductions, which together place many of the quickly changing conversational topics into context"--Publisher's description.
Vol. 1 Nos 1 to 8 (February 1818 to March 1820) Vol. 2 Nos 9 to 16 (March 1820 to September 1820) Vol. 3 Nos 17 to 31 (May 1822 to May 1823) Vol. 4 Nos 32 to 43 (May 1823 to September 1823) Vol. 5 Nos 44 to 59 (October 1823 to March 1824)
Includes bibliographical references and index.
Keywords: 19th Century (1801-1900); Composer; Correspondence; Biography; Deafness; Austria